The Influence of Leadership Style and Work Discipline on Employee Performance - Harsono, Yhonanda; Fajarianto, Otto; Afriani, Linda (IJESS International Journal of Education and Social Science, 2024)
This research aims to determine the influence of leadership style and work discipline on employee performance at CV. Anamuda Bogor either partially or simultaneously. The research method used is associative with a quantitative approach. The sample in this study was 50 people. With saturated sampling analysis techniques. The data uses validity tests, reliability tests, classical assumption tests, multiple linear regression analysis, multiple coefficient analysis, coefficient of determination analysis and hypothesis testing. Partially testing the hypothesis for the leadership style variable (X1), obtained t count > t table or (7.501 > 2.011), thus H01 is rejected. Ha1 is accepted, meaning that there is a significant influence between leadership style on employee performance at CV. Anamuda Bogor. Partially testing the hypothesis for the work discipline variable (X2) obtained t count > t table or (5.725 > 2.011) thus H02 was rejected. Ha2 was accepted, meaning that there is a significant influence between work discipline on employee performance at CV. Anamuda Bogor. The correlation value or level of relationship between the independent variable and the dependent variable is 0.793, meaning it has a strong relationship. The coefficient of determination or contribution of simultaneous influence is 62.8%, while the remaining 37.2% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (39.729 > 3.200) thus H03 was rejected. Ha3 was accepted. This means that there is a significant simultaneous influence between leadership style and work discipline on employee performance at CV. Anamuda Bogor.